Assessment of the damage index and its dynamics in patients with non-systemic variants of juvenile arthritis during the treatment with biologics - Z. A. Kolkhidova; I. P. Nikishina; S. I. Glukhova (Научно-практическая ревматология)
Juvenile idiopathic arthritis (JIA) is characterized by a high risk of joint destruction, extra-articular changes, and rapidly progressive disability. The CHAQ (Childhood Health Assessment Questionnaire) questionnaire and X-ray are often used to assess functional impairment and the degree of irreversible damage, but both methods have limitations. The Juvenile Arthritis Damage Index (JADI) has been developed to comprehensively assess the biological prognosis of JIA, which includes articular (JADI-A) and extra-articular (JADI-E) damage evaluation. The use of the JADI may be an effective tool for predicting and monitoring the effectiveness of JIA therapy in real clinical practice conditions.The aim – to identify correlations of the JADI index with features of clinical manifestations in patients with non-systemic variants of JIA who had no experience with biologic therapy (B) and to evaluate the impact of lesions defined through the JADI damage index value on predicting response to B.Methods. This open prospective study included 150 children with non-systemic JIA variants with no history of biologic therapy. The mean age was 12.2±4.6 years, 60% were girls. 112 patients were examined in dynamics after 6 or 12 months from the beginning of B therapy. Clinical and anamnestic evaluations, including detailed assessment of joint status and JADI-A and JADI-E scores, were performed on all patients.Results. The study found that 50% of patients had damage on the JADI score, with 43% having JADI-A+ and 23% having JADI-E+. Both articular and extra-articular damage were present in 15% (n=23) of children. Among those with JADI-A, flexion contractures of the knee joints were most frequently noted in 39%, elbow joints in 28%, and limitation of movement in the cervical spine in 26%. Extra-articular injuries were more frequently presented as avascular necrosis of bones, confirmed by imaging methods (41%), and a significant difference in limb length was observed in 35% of patients. The presence of articular changes was significantly associated with positivity for antinuclear antibody , rheumatoid factor, and anticyclic citrullinated peptide, as well as the absence of enthesitis, elevated erythrocyte sedimentation rate and С-reactive protein, high clinical activity, Juvenile Arthritis Disease Activity Score, CHAQ values, a history of glucocorticoid therapy, and low adherence to treatment. Polyarticular onset involving small hand joints and a tendency for rapid contracture formation were also associated with positive JADI-A values. The onset of polyarthritis with involvement of the small joints of the hands and a tendency to fast contracture formation were also associated with JADI-A positivity. As a result of therapy with B prescribed in routine clinical practice, the vast majority of patients achieved stable status without signs of damage or the value of the damage index remained unchanged. In 26 (23%) patients, JADI-A scores improved with complete resolution of contractures or increased amplitude of joint movement. In 10 (9%) cases there was progression of the lesions with no established correlation with the choice of a specific drug, including 6 (5%) children with irreversible changes despite the use of targeted therapy.Conclusions. The JADI index is a useful and accessible tool for clinical assessment of articular and extra-articular lesions, reflecting the prognosis of JIA and an objective indicator of therapy efficacy.